Conservatism and liquidity traps - Sebastian Schmidt; Taisuke Nakata (European Central Bank (ECB), 2015)
In an economy with an occasionally binding zero lower bound (ZLB) constraint, the anticipation of future ZLB episodes creates a trade-off for discretionary central banks between inflation and output stabilization. As a consequence, inflation systematically falls below target even when the policy rate is above zero. Appointing Rogoff's (1985) conservative central banker mitigates this deflationary bias away from the ZLB and enhances welfare by improving allocations both at and away from the ZLB.
Keywords: E52; E61; 330; Deflationary Bias; Inflation Conservatism; Inflation Targeting; Liquidity Traps; zero lower bound